2014
DOI: 10.1108/jkm-08-2013-0324
|View full text |Cite
|
Sign up to set email alerts
|

The barriers of knowledge generation, storage, distribution and application that impede learning in gas and petroleum companies

Abstract: Purpose – This paper aims to find and rank the barriers of the four knowledge management (KM) processes including generation, storage, distribution and application in the gas and petroleum sector. Design/methodology/approach – Reviewing the literature of KM and organizational learning, this paper extracted all of the barriers which impede KM processes. Then it designed a questionnaire for validating, ranking and categorizing barriers. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 69 publications
(162 reference statements)
4
43
0
1
Order By: Relevance
“…This study reveals that embeddedness and explicitness of knowledge are important factors in determining KSB, which helps in understanding the nature of the knowledge to be shared (Cummings & Teng, ). The analysis supports prior empirical studies (Cummings & Teng, ; Kim & Lee, ; Ranjbarfard et al, ) to show the importance of organisational and technological factors in determining the KSB of the employees of organisations. The nature of knowledge and the environment of the PSUs (from organisational and technological perspectives) are prerequisites for motivating KSB among employees (Yang, ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This study reveals that embeddedness and explicitness of knowledge are important factors in determining KSB, which helps in understanding the nature of the knowledge to be shared (Cummings & Teng, ). The analysis supports prior empirical studies (Cummings & Teng, ; Kim & Lee, ; Ranjbarfard et al, ) to show the importance of organisational and technological factors in determining the KSB of the employees of organisations. The nature of knowledge and the environment of the PSUs (from organisational and technological perspectives) are prerequisites for motivating KSB among employees (Yang, ).…”
Section: Discussionsupporting
confidence: 86%
“…The measure for contextual factors has been adopted using six items (EC1–SRC4; four items each for environmental and source and recipient context and three items each for knowledge and relational context) from the studies of Ranjbarfard et al () and Cummings and Teng (); for example, “There is well coordination between different departments of the organisation” and “Differences in my knowledge base and that of my immediate senior/junior managers, make knowledge‐sharing difficult.”…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the theoretical perspective, it is one of the first studies analysing KM process barriers in oil industry, making possible to outline future research directions on this topic. Our study validates the findings of other studies addressing the KM process barriers, like Ranjbarfard et al [70], Patil et al [4] or Wong and Aspinwall [9] regarding the typology of barriers they identified, even though a different set of barriers were considered in our own research.…”
Section: Discussionsupporting
confidence: 80%
“…Absorptive capacity describes, in this case, the ability to identify, assimilate, transform, and apply external or new knowledge by each member of the organization [70,109,124].…”
Section: Conceptual Modelmentioning
confidence: 99%